2013
DOI: 10.1177/1356336x13486049
|View full text |Cite
|
Sign up to set email alerts
|

What is recognised as ability in physical education? A systematic appraisal of how ability and ability differences are socially constructed within mainstream secondary school physical education

Abstract: In sport, schools and physical education (PE) ability has invariably been understood as an inherent and relatively immutable capacity, amendable to varying degrees by interventions such as training regimes and education. Differences in achievement are assumed to be an inevitable consequence of natural variations in ability and an indication of motivation or effort. Drawing on the theoretical tools of Pierre Bourdieu, Evans, in 2004, proposed an alternative socially constructed perspective of ability. Evans sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…For example, these 'subversions' may be evidenced in particular contexts in relation to changing and inconsistent attitudes towards gender within PE and sport (Hills, 2006). The concept of habitus has primarily been used to explain and critique the continuity of teaching practices and normative understandings of desirable physical capital within PE in the broader context of Bourdieu's work on reproduction; subsequently, the conceptual and practical considerations involved in changing habitus remain contested (Green, 2002;Hay & MacDonald, 2010a;Wilkinson, Littlefair, & Barlow-Meade, 2013).…”
Section: Bourdieumentioning
confidence: 99%
“…For example, these 'subversions' may be evidenced in particular contexts in relation to changing and inconsistent attitudes towards gender within PE and sport (Hills, 2006). The concept of habitus has primarily been used to explain and critique the continuity of teaching practices and normative understandings of desirable physical capital within PE in the broader context of Bourdieu's work on reproduction; subsequently, the conceptual and practical considerations involved in changing habitus remain contested (Green, 2002;Hay & MacDonald, 2010a;Wilkinson, Littlefair, & Barlow-Meade, 2013).…”
Section: Bourdieumentioning
confidence: 99%
“…This would involve a reconsi-deration of the personal characteristics -either acquired and/or learned based on individuals' class and culture -that are configured as desirable by powerful agents in the field, and thus, are per-ceived as abilities (Evans, 2004). Wilkinson et al's (2013) findings have made a significant contribution to understandings of ability in PE and the educational consequences of narrow conceptions of ability, and their research has underpinned the development of effective and inclusive practices and equity agendas (Evans and Davies, 2017). However, their work focuses solely on PE, and they only included research informed by the work of Evans (2004).…”
Section: Introductionmentioning
confidence: 99%
“…In light of the above limitations, this study aims to systematically review the key literature in this area to address the gaps identified in Wilkinson et al's (2013) work, with a particular focus on PETE. The reasons for this are twofold: (a) it is an appropriate context to challenge some of the unquestioned internal beliefs held by many future educators (Brown, 2005); and (b) PETE pro-vides an ideal space for generating critical debate on how future educators might deal with the differences children bring to PE, which is an imperative issue for the successful implementation of inclusion (Evans and Penney, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Narrow and reductionist views typically center on performances in specific activities, often derived from sport and exercise contexts, which are usually measured and valued in relation to explicit or implicit standards of excellence. This perspective of ability tends to privilege certain students and marginalize others, often equating ability with technique-based sport performance (Tidén, Redelius, and Lundvall 2017;Wilkinson, Littlefair, and Barlow-Meade 2013). Marginal attention is put on what there is to know when you can perform a specific movement.…”
Section: Introductionmentioning
confidence: 99%